2010
DOI: 10.1007/s11738-010-0588-5
|View full text |Cite
|
Sign up to set email alerts
|

Silicon enhances photochemical efficiency and adjusts mineral nutrient absorption in Magnaporthe oryzae infected rice plants

Abstract: Silicon (Si) has been verified to play an important role in enhancing plant resistance against pathogens, but the exact mechanisms remain unclear. Two near-isogenic lines of rice (Oryza sativa L.), CO39 (blast susceptible), and C101LAC (Pi-1) (blast resistant), were hydroponically grown to study the effects of exogenous silicon application on the changes of disease incidence, mineral nutrient concentrations, chlorophyll content, and photochemical efficiency in Magnaporthe oryzae infected rice plants. Si amendm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 54 publications
(67 reference statements)
3
26
1
Order By: Relevance
“…High numbers for LAI appear to produce the best yields, and early signs of good leaf growth can predict yield. These results are in agreement with those of Amer (2010) working on corn and Amer (2011) on squash, also this finding was noted earlier in some crop plants (Degu et al, 2008;Gao et al, 2011;Habibi, 2012). HI recorded under FS (0.54) was higher than under SS (0.42) by 28.6% (Table 8) the same trend was obtained by Amer (2011) on squash and Wajid (1990) on corn.…”
Section: Effect Of Growing Season and Deficit Irrigation On Growth Pasupporting
confidence: 92%
“…High numbers for LAI appear to produce the best yields, and early signs of good leaf growth can predict yield. These results are in agreement with those of Amer (2010) working on corn and Amer (2011) on squash, also this finding was noted earlier in some crop plants (Degu et al, 2008;Gao et al, 2011;Habibi, 2012). HI recorded under FS (0.54) was higher than under SS (0.42) by 28.6% (Table 8) the same trend was obtained by Amer (2011) on squash and Wajid (1990) on corn.…”
Section: Effect Of Growing Season and Deficit Irrigation On Growth Pasupporting
confidence: 92%
“…However, in sharp contrast with the results of the present study, Gao et al. () reported a positive effect of Si on the photochemical efficiency (evidenced by a lower decrease in the F v / F m values and high concentration of photosynthetic pigments) for rice plants infected by P. oryzae . Similarly, the infection of rice and sorghum plants by B. oryzae and C. sublineolum , respectively, impaired photosynthesis, but for a lesser extent on plants supplied with Si (Dallagnol et al., ; Resende et al., ).…”
Section: Discussioncontrasting
confidence: 99%
“…() demonstrated that A values were less compromised due to an increase in foliar Si concentration (FSC) of rice plants infected by Bipolaris oryzae . Additionally, on rice plants supplied with Si and infected by Pyricularia oryzae , the values of the maximum photochemical efficiency of the photosystem II (PSII) ( F v / F m ) were similar to the ones obtained from noninfected plants nonsupplied with Si (Gao et al., ).…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations